Consensus and criminal proceedings in Brazil: plea bargain in the Anti-Crime Package (Research, Society and Development, 2022)
The plea bargain consists of a negotiating institute, through which the disputing parties, after the formation of consensus, reach an agreement, without the need to go to trial. This article analyzed the difficulty of accepting the aforementioned institute in the Brazilian legal system, due to the non-acceptance of art. 395-A, during the processing of Bill number 882/2019. With this, this research aimed to understand the difficulty that national criminal procedural actors have in dealing with criminal proceedings, which is one of the probable causes of the non-approval of the plea bargain by the Brazilian parliament. As a methodology, applied research was used, with a hypothetical-deductive approach, based on books and scientific articles, bibliographical research to support knowledge about plea bargaining and other consensual institutes and exploratory research in the analysis of the processing of bills that deal with the topic. Thus, the applicability of plea bargaining in North American law was analyzed, where this system emerged and became a tradition in the country's legal system. Still, it examined the consensual institutes of the criminal transaction, the conditional suspension of the process and the agreement of non-criminal prosecution, which are already in force in the Brazilian judicial system. It was used as a hypothesis perspective present in sectors of legal anthropology in Brazil in the sense that there is a difficulty, ethnographically verifiable, in the actors of our legal system in dealing with consensual solutions in criminal proceedings. Considering the limits of this work, it was possible to demonstrate that there is difficulty in accepting consensual solutions in criminal proceedings in Brazil.